COVID-19 Mortality in Children: A Referral Center Experience from Iran (Mofid Children’s Hospital, Tehran, Iran) - Shahnaz Armin; Seyed Alireza Fahimzad; Sedigheh Rafiei Tabatabaei; Roxana Mansour Ghanaiee; Noushin Marhamati; Seyyedeh Narjes Ahmadizadeh; Azita Behzad; Seyedeh Masumeh Hashemi; Saeed Sadr; Maryam Rajabnejad; Mahnaz Jamee; Abdollah Karimi (Canadian Journal of Infectious Diseases and Medical Microbiology)
Background. The novel coronavirus disease 2019 (COVID-19) started in Wuhan, China, in December 2019. It spread widely around the world and was described as a pandemic by the World Health Organization (WHO). The knowledge regarding the mortality rate and risk factors of COVID-19 among the pediatric population is lacking. In this regard, we aimed to report the clinical and laboratory characteristics of deceased pediatric patients with SARS-CoV-2 infection. Method. This cross-sectional study was conducted in Mofid Children’s Hospital, Tehran, Iran, from February 2020 to April 2021. Recorded documents of 59 pediatric patients (under 18 years old) assumed to have COVID-19 who had died in the COVID-19 ward and COVID-19 intensive care unit (ICU) were retrospectively evaluated. All statistical analyses were performed using SPSS software (v. 26.0, Chicago, IL). A P value of less than 0.05 was considered statistically significant. Results. From 711 COVID-19 definite and suspected patients, 59 children died. Of these deceased pediatric patients, 34 were boys (57.62%) and 25 were girls (42.37%), with a total mean age of 5.6 years. The median length of stay in the hospital was 10 days (range 1–215). 91.52% had underlying comorbidities of which neurological diseases accounted for the largest share. 54 patients were admitted to the ICU and 83.05% of them had intubation during their hospitalization. In addition, the most common reasons for death in our study were related to respiratory and multiorgan failure. Conclusion. According to our knowledge, we are the first team to report such a thorough study in the field of COVID-19 pediatric mortality in Iran. Mortality was observed in all age groups of children, especially in those with previous comorbidities, specifically neurological disease. Abnormally elevated tests of ESR, CRP, LDH, AST, and ALT as well as the presence of proteinuria and hematuria were found in more than 50% of patients in our investigations, and ICU admission between both definite and suspected groups had significant differences, so monitoring and considering these factors may help to control and reduce the progression of the disease to death.